MENGOLAH INFORMASI DALAM MEDIA INTERAKTIF MENGGUNAKAN APLIKASI SWISHMAX - Kamaludin, Kamaludin (BACA: Jurnal Dokumentasi dan Informasi, 2025)
Author tries to explain how to manage the scientific articles by using SwishMax application in this paper. Many navigations inside the program are described in this paper with some examples. This navigation will make users easy to find the information which is needed. The method of this paper is based on literature study. Some of the literatures were then analyzed to describe the advantages in the information processing on interactive media. Author also tries to describe how to make navigations requested by user.